Endoscopic direct vessel closure in carotid artery injury. Issue 3 (10th December 2014) - Padhye, Vikram; Murphy, Jae; Bassiouni, Ahmed; Valentine, Rowan; Wormald, Peter‐John
<x xml:space="preserve">Abstract</x> Background Internal carotid artery (ICA) injury represents one of the most challenging management scenarios for the endoscopic skull base surgeon. Techniques developed through use of an animal model of carotid injury have shown direct vessel closure techniques to be effective in gaining hemostasis and preventing subsequent complications. The aim of this study was to investigate the effectiveness of the novel AnastoClip vessel closure system in ICA injury. Methods Nine sheep underwent ICA dissection/isolation followed by the artery placement within a modified "sinus model otorhino neuro trainer" (SIMONT) model. Standardized linear injuries were made and treated endoscopically with the AnastoClip device. Specific outcome measures included attainment of primary hemostasis, procedure time, blood loss, pseudoaneurysm formation and carotid patency on follow‐up magnetic resonance imaging (MRI). Results Primary hemostasis was achieved in all cases. No instances of secondary bleeding. Procedure times averaged 5 minutes and 25 seconds. Average blood loss was 146 mL. All 9 sheep reached the 3‐month end point. Eight showed normal carotid flow on MRI, with 1 case of pseudoaneurysm. Conclusion Direct vessel closure is an effective endoscopic technique in ICA injury. It allows for visual confirmation of hemostasis and carotid flow and permits the surgeon to continue with surgery despite the complication. The novel design of the AnastoClip can maintain normal vessel patency as well as accommodate pulsatile flow.